Culturally-Based Islamic Character Education Management in Addressing the Moral Crisis At SD IT Alam Nurul Islam Yogyakarta - Endah Saraswati; Bambang Sudarsono; Enung Hasanah (Bulletin of Community Engagement, 2026)
This study aims to analyze Islamic culture-based character education management in addressing the moral crisis among students at SDIT Alam Nurul Islam in Yogyakarta. This moral crisis, characterized by a decline in discipline, responsibility, and manners, poses a major challenge in elementary education. The study employs a qualitative approach with a case study design. The research subjects include the school principal, teachers, educational staff, students, and parents, selected through purposive sampling. Data collection techniques include in-depth interviews, participatory observation, and document analysis. Data analysis utilizes an interactive model comprising data reduction, data presentation, and drawing conclusions. The research findings indicate that: (1) character education planning is conducted integrally based on the values of the Qur’an and Sunnah; (2) organization is carried out collaboratively through a clear structure and a dual-teacher system; (3) the implementation of character education is conducted through religious habit formation and experiential learning; (4) monitoring is conducted through authentic behavior-based evaluation; and (5) success is influenced by synergy between schools and parents, while obstacles stem from the family environment and digital media. These findings confirm that integrated and collaborative Islamic culture-based character education management is effective in responding to students’ moral crises in a systemic and sustainable manner.